PENGARUH NPM, FDR, KOMITE AUDIT, PERTUMBUHAN USAHA, LEVERAGE DAN SIZE TERHADAP MANAJEMEN LABA - Mahfudzotun Nahar; Teguh Erawati (AKUNTANSI DEWANTARA, 2017)
The purpose of this study was to know the influence of NPM , FDR, Audit Committee, the sales growth (growth), leverage and size of the company earnings management practices of Islamic banking in Indonesia. The dependent variable used in this study was calculated using the earnings management of discretionary accruals. The independent variables used in this study is the net profit margin ratio, the ratio of Financing to Deposit Ratio, the Audit Committee, Sales Growth (Growth), Leverage and Firm Size.            The sample in the study of Islamic banking, comprising both Sharia Bank or Sharia in commercial banks by the Financial Services Authority statistics as of June 2015. The sample was selected using purposive sampling was then obtained 6 Islamic Banks and 12 Sharia sampled in this study ,            The results of this study indicate that there is significant influence between NPM ratio to earnings management of Islamic banking. As for the ratio of FDR, the Audit Committee, Growth, Leverage and Size (size of the company) had no significant effect on earnings management practices in Islamic banking.Keywords: earnings management, NPM, FDR,audit committee, Growth, Leverage, Company Size